Electrochemical Investigation of Thiophene on Glassy Carbon Electrode and Quantitative Determination of it in Simulated Oil Solution by Differential Pulse Voltammetry and Amperometry Techniques - Mojtaba Mostafavi, S.; Rouhollahi, Ahmad; Adibi, Mina; Mohajeri, Ali; Pashaee, Farshid; Pyriaee, Masoumeh (Asian Journal of Chemistry, 2011)
In this study, the electrooxidation of thiophene was investigated by cyclic voltammetry in acetonitrile solution on glassy carbon electrode (GCE). It was been observed that electrooxidation of thiophene in acetonitrile is completely irreversible on glassy carbon electrode surface. For thiophene, a sharp oxidation peak at 2.06 V is obtained at glassy carbon electrode in acetonitrile media with 1 mM of TBAPF6 as support. The diffusion constant was also calculated by chronoamperometry. Differential pulse voltammetry and amperometry were used for the determination of thiophene in acetonitrile media. Quantitative determination of thiophene was done by using calibration curve of anodic peak current of differential pulse voltammetry and amperometry versus concentration in concentrative range 2.0 × 10-7 to 1.0 × 10-6 and RSD < 3.0 %. This method is also used for determination of thiophene in simulated solution including thiophene, dibenzothiophene, thiophenol and some mercaptanes in octane media.